Facet engineering of monodisperse PbS nanocrystals with shape- and facet-dependent photoresponse activity. Issue 109 (9th November 2016) - Zha, Chenyang; Ji, Cheng; Zhang, Junjie; Shen, Liming; Zhang, Xiaoyan; Dong, Shuai; Bao, Ningzhong
Abstract : Monodisperse PbS nanocrystals with three different shapes for designing optoelectronic devices. Abstract : Monodisperse PbS nanocrystals with controlled spherical, octahedral, and cubic shapes were synthesized via simple thermal decomposition of lead–oleate complex precursors by simply changing the synthetic procedure and the Pb and S precursor concentrations. Spherical nanocrystals with mixed facets exposed and octahedral nanocrystals with 111 facets exposed were synthesized through a "hot-injection" process. Cubic nanocrystals with 100 facets exposed were prepared via a "heating-up" growth process. The three types of monodisperse PbS nanocrystals showed shape- and facet-dependent photoresponse behaviors. The thin film of cubic PbS nanocrystals with 100 facets exposed exhibited the largest current enhancement (91.3%) after irradiation as compared with the other two shapes. Meanwhile, the results of density functional theory calculation confirmed that the photoexcited electrons can be driven in the 100 facets with mixed Pb/S atoms through σ bonding consisting of the overlapping s(Pb 6s)–p(S 3p) orbitals. This significantly shortens the carrier transfer distance and reduces the carrier recombination. The present facet engineering strategy can be extended to the other semiconducting nanocrystal syntheses and solar energy conversion applications.